Management of Personal Protective Equipment (PPE) for Laundry Workers in the Linen and Housekeeping Unit at the Jember Plantation Hospital Jember Regency Clinic - Reny Indrayani; Noeroel Widajati; Farha Kamilatun Noha Fadilah (Tadulako University, 2026)
The laundry process involves various complex hazards, including biological, ergonomic, physical, and chemical hazards, this can result in health problem. The Jember Plantation Hospital Clinic is the referral hospital with the highest number of patients in Jember Regency, based on the participant eligibility letter (SEP) of the Jember Regency Health Insurance (BPJS Kesehatan) in 2022. There have been cases of Covid-19 infection spreading among workers in the linen unit. Therefore, the implementation of effective personal protective equipment (PPE) management is an important component in OHS protection efforts. The purpose of this research is to examine the implementation of PPE management among laundry workers in the Linen and Housekeeping Units of the Jember Plantation Hospital Clinic Jember Regency using the legal basis of the Minister of Manpower Regulation No. 8 of 2010 concerning PPE. This study used a qualitative descriptive design. Data collection through observations, interview and literature studies. The research results show that the implementation of PPE management has not been optimal. Inconsistencies were found in determining PPE standards and quality, and the availability of adequate storage facilities. Furthermore, PPE training has not been comprehensively implemented, and worker compliance with PPE use remains low. PPE supervision and inspections tend to focus on compliance, without fully addressing the condition and suitability of the PPE. Systematic and continuous strengthening of PPE management is needed to improve the safety and health of hospital laundry workers.